TRANSITIVE HYPERIDENTITY IN SEMIGROUPS - Hakobyan, T.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
In this paper we characterize all semigroups in which the hyperidentity of transitivity X(X(x, y), X(y, z)) = X(x, z) is polynomially satisfied. In particular, we show that every transitive semigroup (that is a semigroup with the identity xy^2z = xz ) is also hypertransitive.